2014
DOI: 10.1163/22134468-00002019
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Timing and Attention: Modality Effect in Timing with a Break

Abstract: Tones are perceived longer than visual stimuli of same durations. One interpretation of this modality effect is that auditory stimuli capture attention more easily than visual stimuli, resulting in more efficient temporal processing. During a time interval production, expecting a break signal lengthens the produced interval, an effect explained by attention sharing between timing and monitoring for the signal occurrence. In the present study, participants produced a brief time interval defined by a visual or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, participants needed to sum the pre-break and post-break durations. Fortin and Massé [ 11 ] and Viau-Quesnel et al [ 14 ]directly compared with- and without-break conditions, which were similar to the summation and single-stimulus tasks in the present study, respectively. They reported that, in most cases, the reproduced duration was shorter in the with- versus without-break condition.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, participants needed to sum the pre-break and post-break durations. Fortin and Massé [ 11 ] and Viau-Quesnel et al [ 14 ]directly compared with- and without-break conditions, which were similar to the summation and single-stimulus tasks in the present study, respectively. They reported that, in most cases, the reproduced duration was shorter in the with- versus without-break condition.…”
Section: Discussionmentioning
confidence: 77%
“…Although the summation process has not been directly studied, Fortin and colleagues investigated time perception using similar stimulus conditions as the present study [ 11 14 ]. In their studies, participants were required to produce a target duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs with varying positions of intervening stimuli in time discrimination [40]. It is stronger with older than younger adults [41], with visual than auditory stimuli [42], and when participants do not count to aid timing [43]. In short, when attention requirements are higher, effects of expectancy are stronger, which supports an attentional interpretation of the effect.…”
Section: The Generality Of This Expectancy Effect Was Demonstrated Wimentioning
confidence: 84%
“…In concurrent processing studies, participants are asked explicitly to execute two tasks, for example memory search and time production; attention sharing is deliberate, controlled, and effortful, resulting in longer produced intervals. In break experiments [41][42][43]46], produced intervals lengthen proportionally to the duration of expectancy for the break signal, but participants are unaware of sharing attention between timing and expecting the signal. In break experiments, implicit, predictive timing is not related to production of a motor response, but only to interruption in timing, which eliminates the potential influence of motor preparation.…”
Section: The Generality Of This Expectancy Effect Was Demonstrated Wimentioning
confidence: 99%